Effect Of Different Tackifiers On Properties Of Styrene-Grafted Natural Rubber (Snr) And Deproteinized Natural Rubber (Dpnr) Latex Films - Lee, Xing Min (2013)

(untitled)
Styrene-grafted natural rubber (SNR) and deproteinized natural rubber (DPNR) rubber were formulated with coumarone-indene (CI), gum rosin (GR) and petro resin (PR) tackifiers into solution adhesives with toluene as a solvent. Butyl acrylate-grafted starch (MTS) and unmodified starch (UTS) was used as tackifiers in latex adhesives and as fillers in SNR and DPNR composites. The adhesives were subjected to loop tack, peel strength and shear strength tests, and the composites were tested in terms of tensile strength, thermal stability and fracture morphology. The adhesion tests showed that the loop tack and peel strength of the solution adhesives increased up to an optimum loading but decreased their shear strengths with increased tackifier loading. The CI tackifier conferred the highest peel strength in SNR/CI adhesive at 166 N/m and DPNR/CI adhesive at 124 N/m. As tackifier,MTS starch increased the shear strength of SNR and DPNR latex adhesives by fourfold and 65% respectively at 40 parts her hundred rubber (phr) loading. The shear strength improvements was attributed to the improvement of cohesive strength in the SNR and DPNR matrices. MTS and UTS starch incorporation increased the thermal stability of SNR and DPNR composites. SNR/MTS and DPNR/MTS composites exhibited higher tensile strength than UTS composites, which proved that MTS is a reinforcing filler and UTS acts as inert filler. The reinforcement effect of MTS was supported by the fracture morphologies of the SNR/MTS composites, which showed that the MTS particles were significantly smaller than UTS particles.